2000
DOI: 10.1046/j.1537-2995.2000.40020228.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of flow cytometric assays with isotopic assays of 51chromium‐labeled cells for estimation of red cell clearance or survival in vivo

Abstract: Flow cytometry may enable the crude estimation of the percentage of small volumes (<5 mL) of transfused D+ red cells, but in this study it was found that this method was not sufficiently accurate to determine the initial clearance rate, red cell half-life, or mean cell lifespan. If the proportion of transfused cells in the recipient is about 0.2 percent or less, the use of radioisotopes for labeling cells for quantitative in vivo red cell clearance or survival data should remain the method of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…6 However, current cell labels do not measure the life span of an age cohort, but rather, the survival of a randomly labeled RBC sample that contains cells of all ages. For many years 51 Cr, which binds tightly but noncovalently to hemoglobin, [17][18][19] has been the standard label for RBC life span determinations. More recently, biotin has been introduced as a nonisotopic label that is covalently attached to red cell membrane proteins and detected by flow cytometry.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, current cell labels do not measure the life span of an age cohort, but rather, the survival of a randomly labeled RBC sample that contains cells of all ages. For many years 51 Cr, which binds tightly but noncovalently to hemoglobin, [17][18][19] has been the standard label for RBC life span determinations. More recently, biotin has been introduced as a nonisotopic label that is covalently attached to red cell membrane proteins and detected by flow cytometry.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the RBC volume was determined by flow cytometry by exploiting antigen differences between transfused donor RBCs and the recipient's RBCs [89]. Finally, the survival of erythrocytes after transfusion or in patients with autoimmune hemolytic anemia was investigated by labeling RBCs with fluorochromes and subsequent quantification by flow cytometry [90,91].…”
Section: Immunohematologic Diagnostics Rbc Integrity and Immunologymentioning
confidence: 99%
“…Early studies found FC to be superior to a differential agglutination method [98] and comparable to a 51 Cr survival study [99]. [106], and anti-D [107]. Most of these studies used FC to follow the survival of one or more whole units of blood.…”
Section: Detection and Quantitation Of Red Blood Cell Antigensmentioning
confidence: 99%